Witches' broom disease of cassava is associated with a fastidious fungal pathogen in Southeast Asia - Arinaitwe, W; Vongphachanh, P; Chittarath, K; HangLe, T; Oeurn, S; Malik, I; Newby, J; Sophearith, S; Youabee, L; Leiva, A; Pardo, J; Cuellar, W (2023)
Cassava Witches' Broom Disease (CWBD) is a threat to cassava (Manihot esculenta) in mainland Southeast Asia (SEA). The prevalence of CWBD in the region, which had been low in the previous 5 years, has reached a critical point. CWBD incidence in Lao PDR, Cambodia, Vietnam, and Thailand has been reported at 75% in some cases. CWBD was previously suspected to be caused by a phytoplasma, with limited-to-no detection. There is no biological evidence linking phytoplasma and CWBD. We recently used shotgun sequencing to examine pathogen communities in CWBD-infected and healthy plants. We found that a fungus in the genus Ceratobasidium, 98.3-99.7%, similar to C. theobromae, was conspicuously present in contigs from diseased but not healthy plants. C. theobromae causes vascular streak disease (VSD), one of the major cacao diseases in SEA and challenging to culture in-vitro. We have developed a robust PCR-based assay based on the latest sequence data to support the multiplication of disease-free planting materials and regional wide surveillance. Currently, we are investigating CWBD diversity, disease progression, host range, and transmission pathways to accelerate the development of integrated management options, including breeding for resistance and biochemical control.